2011
DOI: 10.1016/j.bbamem.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Pun1p is a metal ion-inducible, calcineurin/Crz1p-regulated plasma membrane protein required for cell wall integrity

Abstract: Under conditions of environmental stress, the plasma membrane is involved in several regulatory processes to promote cell survival, like maintenance of signaling pathways, cell wall organization and intracellular ion homeostasis. PUN1 encodes a plasma membrane protein localizing to the ergosterol-rich membrane compartment occupied also by the arginine permease Can1. We found that the PUN1 (YLR414c) gene is transcriptionally induced upon metal ion stress. Northern blot analysis of the transcriptional regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
1
11
0
1
Order By: Relevance
“…Integrity of cell walls and membranes are important for cells under stress from biomass-derived inhibitors as these target and disrupt these cellular structures [ 19 ]. CHS5 , FLC1 , PIR1, and PUN1 are important for cell wall biosynthesis and functioning [ 63 67 ]. HES1 encodes a protein that is assumed to be involved in the regulation of the biosynthesis of ergosterol, an important component of yeast cell membranes, which has been shown to be important for the tolerance of various inhibitory compounds, particularly vanillin [ 29 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of cell walls and membranes are important for cells under stress from biomass-derived inhibitors as these target and disrupt these cellular structures [ 19 ]. CHS5 , FLC1 , PIR1, and PUN1 are important for cell wall biosynthesis and functioning [ 63 67 ]. HES1 encodes a protein that is assumed to be involved in the regulation of the biosynthesis of ergosterol, an important component of yeast cell membranes, which has been shown to be important for the tolerance of various inhibitory compounds, particularly vanillin [ 29 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in S. cerevisiae a sur7 ∆ mutation causes weaker phenotypes than in C. albicans , related observations have been reported, such as greater susceptibility to osmotic stress [ 125 ]. Other work with S. cerevisiae demonstrated that Pun1, a paralog of Sur7, is induced upon cell wall damage, and pun1 ∆ mutant cells have modified cell walls [ 126 ]. The pun1 ∆ cells are more sensitive to the cell wall degrading enzyme zymolyase, which correlates with other results indicating that the mutant cells have reduced levels of 1,3-β- d -glucans and mannoproteins [ 126 ].…”
Section: Mcc/eisosomes Protect Against Stressmentioning
confidence: 99%
“…Other work with S. cerevisiae demonstrated that Pun1, a paralog of Sur7, is induced upon cell wall damage, and pun1 ∆ mutant cells have modified cell walls [ 126 ]. The pun1 ∆ cells are more sensitive to the cell wall degrading enzyme zymolyase, which correlates with other results indicating that the mutant cells have reduced levels of 1,3-β- d -glucans and mannoproteins [ 126 ]. Eisosomes have also been shown to play a role in surviving hypo-osmotic stress in S. pombe protoplasts [ 23 ].…”
Section: Mcc/eisosomes Protect Against Stressmentioning
confidence: 99%
“…A more subtle Mn 2+ -Ca 2+ interplay exists though, being manifested at several levels [41]. For example, high Mn 2+ is controlled by calcineurin/Crz1pregulated Pmr1p and Pun1p [100]. Importantly, the tolerance of yeast cells to Mn 2+ is related to both Pmr1p and Vcx1p [41,64,65,101] two determinants of maintaining low [Ca 2+ ] cyt by transporting the ions to the vacuole and Golgi/ER, respectively [60][61][62][63].…”
Section: Mn 2+mentioning
confidence: 99%